Microsoft® SharePoint® 2010 : creating and implementing real-world projects - Mason, Jennifer (O'Reilly Media, 2012)
"Build effective solutions for real-world business scenarios--using out-of-the-box tools in Microsoft® SharePoint® Server, SharePoint Foundation, and Office 365. Each chapter in this hands-on book focuses on a single business project, using a standard approach to guide you through the solution-building process from start to finish. Apply your skills as a SharePoint power user or site administrator--and get started now"--Provided by publisher.